The Party's Viewpoints and Government's Policies on the Migration of Ethnic Minority Groups: Achievements and Problems - Tan, Nguyen Dinh (VNU Journal of Science: Policy and Management Studies; Vol 34 No 2, 2018)
The Party's viewpoints and policies are consistent with the policies of equality, solidarity, mutual respect and mutual assistance among ethnic groups, creating conditions for ethnic groups to develop together with the development of the whole community of ethnic groups in Vietnam. The Party and the government have promulgated several programs and policies aimed at ensuring better life for ethnic people. The programs and projects focused on settling population re-planning, re-settling people from high mountainous areas to lower areas; inter-provincial, intra-regional migration, and migration in the North-Central Highlands and Southeast region to improve the living standards of the people, especially ethnic minorities in remote and mountainous areas. This paper also examines some of the existing studies on ethnic minority migration, achievements and issues that need to be further explored. The overall objective of the paper is to assess the effectiveness of migration policies, the situation of migration of ethnic minorities from 1986 to present and to propose possible solutions and migration policies to contribute to sustainable development and ensure national defence and security of ethnic minority areas until 2030. Keywords: Party's viewpoints, government's policies, migration of ethnic minority groups.